The Implementation of Augmented Reality in Internet of Things for Virtual Learning in Higher Education - Aroba, Oluwasegun Julius (International Journal of Computing Sciences Research, 2024)
Purpose – This article investigates the potential of augmented reality (AR) for virtual learning in higher education. This review discusses the advantages as well as disadvantages of virtual learning, as well as the advantages and functions of augmented reality in digital literacy on innovative education. With the launch of electronic literacy about two years ago during the COVID-19 epidemic, considerable changes in literacy and tuition methods in higher education have previously occurred. It has become clear that virtual literacy issues are far worse than actual literacy issues. To meet the needs of today's scholars and establish novel tutoring approaches, educational institutions must implement new literacy technology, such as augmented reality. By implementing nascent literacy technology, this investigation hopes to lead to a better comprehension of stoked reality in virtual literacy for advanced education researchers. Method – The goal of this essay is to investigate the use of augmented reality in higher education for virtual learning. The moderate category of this technology will also be investigated. Head-mounted displays are occasionally used in conjunction with real-world environments or props, such as when simulating takeoff on a motion platform; however, augmented reality makes reading and teaching methods far more accessible. Results – Similarly, a use case was created to demonstrate the student journey using stoked reality software on the mobile device to fantasize, comprehend, and make learning more accessible for students to engage with their environment. Conclusion –      Augmented reality has the potential to identify educational surroundings as far more accurate, acceptable, more unifying than digital illiteracy. Increased reality technology affects literacy and the higher education system. It possesses the possibility of increasing the approachability and accessibility of literacy sources in team and personal study. Recommendations – To successfully integrate augmented reality into the Internet of Things for virtual learning in higher education, organizations need to put a high priority on staff development, make significant infrastructure investments, and foster cross-disciplinary collaboration. Practical Implications – Higher education institutions should prioritize data security and ethical issues while simultaneously investing in faculty development and AR-IoT infrastructure.